COMPARATIVE ANALYSIS OF K-MEANS, X-MEANS AND K-MEDOIDS IN CLASSIFYING MARRIAGE CHOICED ADMIST QUARTER-LIFE CRISIS - Ariza, Disya Nurul; Ningsih, Rahayu; Muryani, Sri; Ferliyanti, Herlina; Wahidin, Ahmad Jurnaidi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2024)
Abstract: Bekasi Regency, being one of the key cities in Indonesia, offers a suitable setting to study the intricacies of marriage decision-making during a quarter-life crisis. This study focuses on the application of clustering algorithms to categorize individuals based on their marriage choices. Data was collected from a questionnaire completed by 110 respondents from Bekasi Regency, specifically individuals aged 18 to 30 who are single, including 80 women and 30 men. Data analysis was conducted using the RapidMiner software to evaluate the effectiveness of three clustering algorithms K-Means, X-Means, and K-Medoids in categorizing marriage decision patterns among young people experiencing a Quarter Life Crisis in Bekasi Regency. Results indicate that each algorithm has its own strengths and limitations in handling Quarter Life Crisis data.The results of the analysis show that the K-medoids algorithm provides the best clustering results with the lowest DBI value of 0.195, followed by the X-Means algorithm with a value of 0.199 and K-Means with a value of 0.207. These results can help understand the pattern of marriage decisions in the Quarter Life Crisis phase and help provide insights for policymakers in Bekasi Regency to make more effective intervention programs. Keywords: K-Means; K-Medoids; X-Means Abstrak: Sebagai salah satu kota besar di Indonesia, Kabupaten Bekasi memberikan konteks yang tepat untuk mempelajari kompleksitas pengambilan keputusan pernikahan di tengah krisis seperempat usia. Penelitian ini berfokus pada pemanfaatan algoritma clustering untuk mengelompokkan individu berdasarkan pilihan pernikahan mereka. Data diambil dari kuesioner yang diisi oleh 110 responden di Kabupaten Bekasi, yang terdiri dari individu lajang berusia 18 hingga 30 tahun, yaitu 80 perempuan dan 30 laki-laki. Analisis data dilakukan dengan perangkat lunak RapidMiner untuk mengevaluasi efektivitas tiga algoritma pengelompokan—K-Means, X-Means, dan K-Medoids—dalam mengelompokkan pola keputusan pernikahan di kalangan pemuda yang menghadapi Quarter Life Crisis di Kabupaten Bekasi. Hasilnya menunjukkan bahwa setiap algoritma memiliki keunggulan dan kelemahannya masing-masing dalam memproses data Quarter Life Crisis. Hasil analisis menunjukkan bahwa algoritma K-medoids memberikan hasil clustering terbaik dengan nilai DBI terendah yaitu 0.195, diikuti oleh algoritma X-Means dengan nilai 0.199 dan K-Means dengan nilai 0.207. Hasil ini dapat membantu memahami pola keputusan menikah pada fase Quarter Life Crisis dan membantu memberikan wawasan bagi pembuat kebijakan di Kabupaten Bekasi membuat program intervensi yang lebih efektif. Kata kunci: K-Means; K-Medoids; X-Means